OPTIMALISASI KURIKULUM MERDEKA: PERAN MEDIA PEMBELAJARAN DIGITAL PADA PENDIDIKAN SEKOLAH DASAR - Nurul A'yun; Nur Ummi Afifah; Sri Wardani; Nuni Widiarti; Panca Dewi Purwati; Arif Widiyatmoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The development of the Industrial 4.0 era and society 5.0 brings changes in human life on a technological basis. Changes in the development of education lead to changes in the curriculum as the life of the course of education. The independent curriculum with the concept of independent learning seeks to answer the challenges of changing times. The development of learning in an independent curriculum seeks to provide teacher flexibility in providing learning that is relevant to the current digital era. This writing aims to find out the realization of the use of digital media in learning in elementary schools. This writing uses the Systematic Literature Review method with systematic and clear steps. The results of the review show that the use of digital learning media in the independent curriculum has a significant positive impact on the quality of learning. However, there are still challenges and obstacles in its implementation.